P129 Estimating Service Capacity for Commissioning an Anticoagulation Service in Line with NICE Guidance in the NHS, England. (15th August 2013) - Moran, D; Griffiths, P; Moore, V
Abstract : Background: Improving quality, patient outcomes and cost effectiveness is an assumed aim of health and social care commissioning. A key aspect for commissioners in the planning phase of the commissioning cycle for an anticoagulation service, in line with NICE guidance, is the ability to estimate the level of service that will be required in order to appropriately commission or decommission services. Objectives: Establish the level of integration of information, alongside clinical and management knowledge, required to successfully calculate appropriate service levels when commissioning or decommissioning an anticoagulation services in the NHS. Methods: A critical appraisal of clinical research studies, epidemiological data, NHS activity data and other information was carried out in combination with clinical and NHS management oversight to inform an estimate of service levels for an anticoagulation service. A systematic literature search of 3 electronic databases, Medline, Embase and Cochrane was carried out. Routinely collected activity data was reviewed through a sample of GP practice systems for primary care information and hospital episode statistics for secondary care information. Healthcare professionals and commissioners with a specialty or interest in an anticoagulation service were consulted. Results: Interim results suggest integration of multiple information sources in combination with clinical and management knowledge produces more robust estimates of service levels for an anticoagulation service. Discussion: The accuracy, and therefore the utility of estimates of service levels for an anticoagulation service will be improved by information linkage, and by using intelligence from multiple sources. This approach could be applied to estimating service levels for other commissioned services.